REPRESENTASI NILAI-NILAI KARAKTER PADA TOKOH IBU DALAM CERITA RAKYAT “TIMUN MAS” - Dewi Lestari; Helviani Helviani; Heri Isnaini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This article describes the character's values on the character of Mother named Mbok Rondo in folklore "Timun Mas". The method used is semiotics approach, data collection technique used is reading text reading to deepen the character possessed by character Mbok Rondo in folklore "Timun Mas". The source of the data comes from a collection of folklore books titled "Timun Mas dan Raksasa", composed by MB.Rahimsyah, AR published by Bintang Indonesia in the first print of 2010. Data processing research is done by looking for a sign that shows the value of characters contained in the sentence , paragraphs, and quotes of dialogue in the folklore. The results obtained from this study show that the character values of Mbo Rondo characters are honest, hard work, creative, disciplined, independent, curiosity, communicative, peaceful, responsible, and religious.